Soil organic carbon dynamics in mountain brown soils under erosion and relief influence - Djalilova, Gulnora; Nurullaev, Azamkhon (Brawijaya University, 2026)
This study investigated the influence of erosion and topographic factors on soil organic carbon (SOC) distribution in mountain brown soils of the Baysun region, Uzbekistan. Soil samples were collected from watershed, midslope, and footslope positions and analyzed using the modified Tyurin method. SOC content ranged from 3.00% in surface horizons of footslope soils to 0.24% in deeper layers of eroded slope soils, indicating substantial carbon depletion under erosion processes. Watershed soils showed relatively stable SOC distribution, while midslope positions were characterized by marked carbon losses. In contrast, footslope areas exhibited SOC accumulation in upper horizons due to depositional processes. The results demonstrated a clear topographic pattern of SOC redistribution along the catena, controlled by erosion and material transport. These findings identified eroded midslope positions as the main hotspots of SOC depletion within the studied mountain catenas. The obtained pattern provides a practical basis for prioritizing soil conservation and degraded-land management measures, including vegetation protection, runoff control, and erosion mitigation in the mountain landscapes of Baysun District.